The Effect of AC (alternating current) and DC (direct current) on Bend Testing Results of Low Carbon Steel Welding Joints - Firmanda, Zetri; Aziz, Abdul; Rahim, Bulkia (Universitas Negeri Padang, 2020)
The purpose of this study was to determine the effect of alternating current (AC) and direct current (DC) on the bend testing results of low carbon steel welding joints. The results of this study are expected to determine the cracks that occur from the root bend and face bend testings in the AC and DC welding process. This study used experimental method, where the research was done by giving AC and direct polarity DC (DC-) SMAW welding treatments. The material used in this research was low carbon steel plate DIN 17100 Grade ST 44, thickness 10 with E7016 electrode type. The process of welding joints used a single V seam, strong current of 90A, and the welding position of 1G. The testing of welding joints was carried out by bend testing using the standard acceptance of AWS D1.1 root bend and face bend testing results. The results of the bend testing showed that the AC welding root bend test specimen held no cracks while the DC welding root bend test held cracks with incompelete penetration and open crack defects. On the contrary, the AC welding face bend test had open crack defects and in the DC welding face bend test was found a crack. Thus, there was a difference in the crack resistance of the welding joint from the types of current used through the root bend test and face bend test. Therefore, it can be summarized that AC welding is better for root welding and DC welding is good for capping welding.